2022
DOI: 10.1098/rsfs.2022.0042
|View full text |Cite
|
Sign up to set email alerts
|

Correlating viscosity and molecular crowding with fluorescent nanobeads and molecular probes: in vitro and in vivo

Abstract: In eukaryotes, intracellular physico-chemical properties like macromolecular crowding and cytoplasmic viscoelasticity influence key processes such as metabolic activities, molecular diffusion and protein folding. However, mapping crowding and viscoelasticity in living cells remains challenging. One approach uses passive rheology in which diffusion of exogenous fluorescent particles internalized in cells is tracked and physico-chemical properties inferred from derived mean square displacement relations. Recentl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 86 publications
3
11
0
Order By: Relevance
“…Such disagreement could be attributed to the excitation wavelength (488 nm versus 900 nm), the different buffers (NaPi versus PBS), the time window (0-50 ns versus 0-24 ns), and the sample preparation (a cuvette versus a droplet) used in both studies. As a control, Lecinski et al 53 also used mGFP as compared with our mEGFP using the enzymatically cleaved GE2.3, where the fluorescence lifetime of mEGFP is known to be approximately 2.6 ns, [46][47][48][49] in relative agreement with our estimated 2P-fluorescence lifetime of 2.75 ns in enzymatically cleaved GE2.3.…”
Section: P-fluorescence Lifetime and Fret Analysis Of Ge23 In Crowded...supporting
confidence: 82%
See 1 more Smart Citation
“…Such disagreement could be attributed to the excitation wavelength (488 nm versus 900 nm), the different buffers (NaPi versus PBS), the time window (0-50 ns versus 0-24 ns), and the sample preparation (a cuvette versus a droplet) used in both studies. As a control, Lecinski et al 53 also used mGFP as compared with our mEGFP using the enzymatically cleaved GE2.3, where the fluorescence lifetime of mEGFP is known to be approximately 2.6 ns, [46][47][48][49] in relative agreement with our estimated 2P-fluorescence lifetime of 2.75 ns in enzymatically cleaved GE2.3.…”
Section: P-fluorescence Lifetime and Fret Analysis Of Ge23 In Crowded...supporting
confidence: 82%
“…Our results are also in general agreement with Lecinski et al qualitatively on the same sensor (crGE2.3) in Ficoll-crowded NaPi buffer. 53 We also demonstrated that the outcome of these studies seems independent of the 2Pexcitation mode of GE2.3 (i.e., single-point versus laser scanning FLIM mode). Such control experiments are rather important since 2P-FLIM is compatible with future 2P-FLIM studies in cultured living cells or even thick tissues as a better model for in vivo studies for mapping the correlation between macromolecular crowding and diseased conditions.…”
Section: Discussionmentioning
confidence: 59%
“…For this theme issue, we gratefully received contributions from across the physics and life sciences with interests in biorheology ranging in length scale from the rheological properties of intracellular biomolecular networks [ 1 , 10 ] to the scale of the direct extracellular environment [ 3 , 7 , 10 , 12 , 13 , 16 ], tissues [ 3 5 ] and even entire organs that actively exert forces onto non-Newtonian fluids [ 6 ]. The mechanical properties at the cellular level are discussed in relationship to cancer [ 2 ], as well as in relationship to the transport of red blood cells in disordered porous environments, be it in vascular networks or in microfluidic devices.…”
Section: Contributed Workmentioning
confidence: 99%
“…To assess this information, the contributed review by Erlich et al [ 4 ] argues it is necessary to develop novel non-perturbative methodologies to probe the network at a small length scale. Lecinski et al address this using single-bead tracking passive rheology in live S. cerevisiae yeast cells [ 1 ], and Jory et al discuss new methodologies to probe mucus adhesion at the microscopic scale using optical tweezers [ 10 ]. Erlich and co-workers also argue the interpretation of the force–displacement measurements in such experiments relies on the development of suitable theoretical models, which face the challenge of linking the molecular topology of the network to the mechanics at the continuum level; such a modelling contribution is provided by Song and co-workers who discuss hyperelastic continuum models [ 3 ].…”
Section: Contributed Workmentioning
confidence: 99%
See 1 more Smart Citation